Optimalisasi Fungsi Masjid sebagai Sentra Pengembangan Wakaf Tunai dalam Meningkatkan Ketahanan Ekonomi Masyarakat Watukebo Jawa Timur - Istikomah, Istikomah; Nur, Siti Khayisatuzahra; Hasanah, Miftahul (Amalee: Indonesian Journal of Community Research and Engagement, 2022)
The purpose of money waqf education activities (productive) activities through community service programs in the East Watukebo Village, Ambulu Jember District was carried out as an effort to provide understanding to the local community about productive, professional, and modern waqf management models. This service activity was carried out with the Muhammadiyah Youth of the East Watukebo Branch Banyuwangi East Java. The implementation method for this activity is through lectures and direct conducted at the An-Nur Mosque. In order to measure the success of the target, in this activity the researcher provided pre-test and post- test instruments taken from the material provided. From the results of the pre-test and post- test that have been carried out, it can be concluded that this activity can increase public understanding regarding productive waqf and its management.